Kapitalizm, praca i podstawa dla historii planetarnych - Chakrabarty, Dipesh (Klio - Czasopismo Poświęcone Dziejom Polski i Powszechnym, 2024)
Translation of the opnening lecture during XXIII International Congress of Historical Sciences (CAPITALISM, WORK, AND THE GROUND FOR PLANETARY HISTORIES)